Method for selecting electrolyte material

The method of evaluating electrolyte materials by assessing the particle hardness of positive electrode active materials in lithium-ion batteries addresses the challenge of capacity deterioration, resulting in improved durability and safety for lithium-ion batteries.

JP2025070521APending Publication Date: 2025-05-02HONDA MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023180901
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is a lack of suitable methods for selecting an electrolyte material that optimally improves the particle strength of the positive electrode active material in lithium-ion batteries, leading to capacity deterioration due to repeated charge and discharge cycles.

Method used

A method involving the use of multiple candidate electrolyte materials to form lithium-ion batteries, which are then charged and discharged under the same conditions. The particle hardness of the positive electrode active material is evaluated, and the electrolyte material corresponding to the highest hardness is selected as the optimal electrolyte material.

Benefits of technology

This method allows for the easy selection of an electrolyte material that effectively improves the particle strength of the positive electrode active material, thereby reducing capacity deterioration and enhancing the durability and safety of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070521000001_ABST
    Figure 2025070521000001_ABST
Patent Text Reader

Abstract

To provide a method for selecting an electrolyte material that can easily select an electrolyte material that is optimal for improving the particle strength of a cathode active material.SOLUTION: A method includes: a charge and discharge step of performing charge and discharge under the same conditions using a plurality of lithium ion batteries for evaluation each containing a plurality of electrolyte candidate materials having ion conductivity and a cathode active material in an unused state; an extraction step of extracting a used cathode active material from each of the plurality of lithium ion batteries for evaluation after undergoing the charge and discharge step; and a selection step of measuring a hardness of the particles of the plurality of used cathode active materials extracted in the extraction step and selecting, as an electrolyte material, the electrolyte candidate material corresponding to the used cathode active material of the highest hardness.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for selecting an optimal electrolyte material to be contained in an electrolyte layer of a lithium ion battery. [Background technology]

[0002] Vehicles such as EVs (Electric Vehicles) and HEVs (Hybrid Electrical Vehicles) are equipped with power storage devices that supply power to motors, etc. The power storage devices are generally provided with a plurality of secondary batteries.

[0003] Lithium-ion batteries (LIBs) are widely used as secondary batteries in EVs and HEVs. Lithium-ion batteries are lightweight and have high energy density, making them ideal for use as high-output power sources in vehicles.

[0004] The capacity of these lithium-ion batteries for vehicles can deteriorate as a result of repeated charging and discharging. One of the causes of this capacity deterioration is the phenomenon in which the particles of the positive electrode active material break down as a result of repeated charging and discharging.

[0005] For this reason, known configurations include selecting a material with high strength as the constituent material of the positive electrode active material, and forming a protective film using constituent components of the electrolyte material to physically protect the particles of the positive electrode active material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2022-510653 Summary of the Invention [Problem to be solved by the invention]

[0007] However, there has been no suitable method for selecting an electrolyte material that is optimal for improving the particle strength of a positive electrode active material, and there has been a need to establish a selection method for appropriately evaluating and selecting electrolyte materials.

[0008] The present invention has been proposed in view of the above-mentioned problems, and aims to provide a method for selecting an electrolyte material that enables easy selection of an electrolyte material that is optimal for improving the particle strength of a positive electrode active material. [Means for solving the problem]

[0009] In light of the above-mentioned background, the present inventors have found that it is possible to select an optimal electrolyte material for preventing capacity degradation by forming evaluation lithium-ion batteries using multiple candidate electrolyte materials, charging and discharging these evaluation lithium-ion batteries under the same conditions, and then evaluating the particle hardness of the positive electrode active material.

[0010] (1) A method for selecting an electrolyte material according to a first aspect of the present invention is a method for selecting an electrolyte material for constituting a lithium-ion battery having a positive electrode having a positive electrode current collector and a positive electrode active material, a negative electrode having a negative electrode current collector and a negative electrode active material facing the positive electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode and containing an electrolyte material, the method comprising the steps of: a charge / discharge step of performing charge / discharge under the same conditions using a plurality of evaluation lithium-ion batteries each containing a plurality of candidate electrolyte materials having ion conductivity and the cathode active material in an unused state; an extraction step of extracting used cathode active material from each of the plurality of evaluation lithium-ion batteries that have undergone the charge / discharge step; and a selection step of measuring the hardness of particles of the plurality of used cathode active materials extracted in the extraction step, and selecting the candidate electrolyte material corresponding to the used cathode active material having the highest hardness as the electrolyte material.

[0011] (2) A second aspect of the present invention is characterized in that, in the method for selecting an electrolyte material according to the first aspect, the positive electrode active material contains a composite oxide of lithium and a transition metal.

[0012] (3) A third aspect of the present invention is the method for selecting an electrolyte material according to the second aspect, characterized in that the transition metal includes at least one of nickel, cobalt, and manganese.

[0013] (4) A fourth aspect of the present invention is the method for selecting an electrolyte material according to any one of the first to third aspects, characterized in that the electrolyte material is selected from a solvent containing either ethylene carbonate or dimethyl carbonate, and a salt containing lithium dissolved in the solvent. Effect of the Invention

[0014] According to the present invention, it is possible to provide a method for selecting an electrolyte material that enables easy selection of an electrolyte material that is optimal for improving the particle strength of a positive electrode active material. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a layer structure of the lithium ion battery of the present embodiment. [Diagram 2] FIG. 4 is an explanatory diagram showing a method for measuring the particle hardness of a positive electrode. [Diagram 3] 1 is a graph showing a load-displacement diagram. [Figure 4] 1 is a graph showing the results of Verification Example 1. [Diagram 5] 13 is a graph showing the results of Verification Example 2. [Figure 6] 13 is an observed image showing the results of Verification Example 3. [Figure 7] 1 is an enlarged SEM observation image showing an example of particle crack determination for positive electrode particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a method for selecting an electrolyte material according to one embodiment of the present invention will be described with reference to the drawings. The following embodiment is specifically described to better understand the gist of the invention, and does not limit the present invention unless otherwise specified. In addition, the drawings used in the following description may show essential parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may not necessarily be the same as the actual ones.

[0017] [Example of lithium-ion battery configuration] First, an example of the configuration of a lithium ion battery to which the method for selecting an electrolyte material of the present invention is applied will be described. FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of a lithium ion battery.

[0018] A lithium ion battery (LIB) 10 is formed by stacking a positive electrode 13 having a positive electrode current collector 11 and a positive electrode active material layer 12 located on one side of the positive electrode current collector 11, a negative electrode 16 having a negative electrode current collector 14 and a negative electrode active material layer 15 located on one side of the negative electrode current collector 14 and facing the positive electrode 13, and an electrolyte layer 17 located between the positive electrode 13 and the negative electrode 16.

[0019] The positive electrode active material layer 12 is a layer containing a positive electrode mixture. The positive electrode mixture contains a positive electrode active material, lithium carbonate, a conductive assistant, and a binder.

[0020] The positive electrode active material absorbs and releases ions, removes and inserts ions (intercalates), or exchanges ions with their counter anions (e.g., PF6 - ) can be used as an electrode active material capable of reversibly undergoing doping and dedoping.

[0021] Specific examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and lithium manganese oxide represented by the general formula: LiNi x Co y Mn zM a O2 (where x + y + z + a = 1, 0 ≤ x < 1, 0 ≤ y < 1, 0 ≤ z < 1, 0 ≤ a < 1, and M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), a composite metal oxide (ternary compound), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (where M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 ), LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), etc., composite metal oxides, polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, etc. Among these, as the positive electrode active material contained in the positive electrode mixture, a ternary compound containing Ni, Co, and Mn is preferred.

[0022] As the binder contained in the positive electrode mixture of the positive electrode active material layer 12, known ones can be used. For example, fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene - hexafluoropropylene copolymer (FEP), tetrafluoroethylene - perfluoroalkyl vinyl ether copolymer (PFA), ethylene - tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene - chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), etc.

[0023] As the conductive assistant contained in the positive electrode mixture of the positive electrode active material layer 12, for example, carbon powders such as carbon blacks, carbon nanotubes, carbon materials, metal fine powders such as copper, nickel, stainless steel, iron, etc., a mixture of carbon materials and metal fine powders, conductive oxides such as ITO, etc. As the positive electrode mixture constituting the positive electrode active material layer 12, among carbon blacks, ketjen black with particularly excellent conductivity is preferred. In addition, when sufficient conductivity can be ensured with only the positive electrode mixture, the positive electrode mixture may not contain a conductive assistant.

[0024] The negative electrode active material layer 15 has a negative electrode active material and a binder as a negative electrode mixture, and may have a conductive assistant as necessary. As the negative electrode active material, a known negative electrode active material can be used. Examples of the negative electrode active material include carbon materials such as metallic lithium, graphite (natural graphite, artificial graphite) capable of occluding and releasing lithium ions, carbon nanotubes, non-graphitizable carbon, graphitizable carbon, low-temperature calcined carbon, etc., metals such as aluminum, silicon, tin, etc. that can combine with lithium, SiO x (0 < x < 2), amorphous compounds mainly composed of oxides such as tin dioxide, lithium titanate (Li4Ti5O 12 ) and the like.

[0025] The conductive assistant and the binder contained in the negative electrode mixture can be the same as those in the positive electrode active material layer 12. In addition to those mentioned in the positive electrode active material layer 12, for example, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyimide (PI), polyamideimide (PAI), polyacrylic acid (PAA), etc. can also be used as the binder used in the negative electrode mixture.

[0026] When charging the lithium ion battery 10 including such a negative electrode active material layer 15, the potential changes as lithium ions enter the interlayer in the carbon material which is an example of the negative electrode active material.

[0027] The electrolyte layer (separator) 17 is located between the positive electrode 13 and the negative electrode 16, permeates lithium ions, and isolates the positive electrode 13 and the negative electrode 16. The electrolyte layer (separator) 17 is composed of, for example, a porous membrane made of a resin material, a non-woven fabric, etc.

[0028] The electrolyte material (electrolyte solution) used in the lithium ion battery 10, which is selected by the method for selecting the electrolyte material of the present invention described later, is composed of a solvent and a salt containing lithium dissolved in this solvent.

[0029] The solvent for the electrolyte is selected from, for example, ethylene carbonate (EC), dimethyl carbonate (DMC), and fluorinated ethers.

[0030] Ethylene carbonate is a glassy solid (room temperature) with a melting point of 34 to 37°C, and is an ester of ethylene glycol with carbonic acid. Ethylene carbonate is a polar solvent, and adding it to the solvent of the electrolyte can increase the dielectric constant.

[0031] Such ethylene carbonate may be contained in a concentration range of 2 mol / L or less relative to 1,2-dimethoxyethane. Alternatively, ethylene carbonate may be contained in a concentration range of less than 8 mass % based on the total solvent.

[0032] By setting the concentration of ethylene carbonate to less than 8 mass % relative to the entire solvent, it is possible to prevent corrosion of aluminum by the electrolyte when, for example, aluminum is used as the positive electrode current collector 11. This makes it possible to further improve the charge / discharge cycle of the lithium ion battery 10.

[0033] Dimethyl carbonate is a water-soluble liquid with a relatively high boiling point (90°C) as an organic solvent. The 1,2-dimethoxyethane may be contained in an amount of 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 25% by mass or less, based on the total mass of the electrolyte. The concentration of 1,2-dimethoxyethane in the electrolyte may be in the range of 3 mol / L or more and 7 mol / L or less.

[0034] When the carbon number of the fluorinated ether is small, the boiling point tends to be low, and the fluorinated ether may evaporate during high-temperature operation of the battery. On the other hand, when the carbon number is too large, the viscosity of the chain ether may increase, and the conductivity of the electrolyte may decrease. Therefore, the carbon number is preferably 4 to 10.

[0035] Specific examples of fluorine-containing chain ethers include 2,2,3,3,3-pentafluoropropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether, 1,1,2,3,3,3-hexafluoropropyl-2,2-difluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, propyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl ether, perfluoropropyl ether, 1H,1H,5H-perfluoropentyl-1,1,2,2-tetrafluoroethyl ether, 1H,1H,2'H-perfluorodipropyl ether, 1H-perfluorobutyl-1H-perfluoroethyl ether, methyl perfluoropentyl ether, methyl perfluorohexyl ether, methyl 1,1,3,3,3-pentafluoro-2-(trifluoromethyl)propyl ether, 1,1,2,3,3,3-hexafluoropropyl 2,2,2-trifluoroethyl ether ethyl nonafluorobutyl ether, ethyl 1,1,2,3,3,3-hexafluoropropyl ether, 1,1,2,3,3,3-hexafluoropropyl 1H,1H-heptafluorobutyl ether, bis(2,2,3,3-tetrafluoropropyl) ether, bis(2,2,3,3,3-pentafluoropropyl) ether, 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether, 1H,1H,2'H-perfluorodipropyl ether, heptafluoropropyl 1,2,2,2-tetrafluoroethyl ether nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,3,3,3-pentafluoropropyl-1,1,2,2-tetrafluoroethyl ether, ethyl nonafluorobutyl ether, methyl nonafluorobutyl ether, 2,2,3,4,4,4-hexafluorobutyl-difluoromethyl ether, 1,1-difluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1-difluoroethyl-1H,1H-heptafluorobutyl ether, bis(1H,1H-heptafluorobutyl) ether, nonafluorobutyl methyl ether, 2,2-difluoroethyl-1,1,2,2-tetrafluoroethyl ether, bis(2,2-difluoroethyl) ether, bis(1,1,2-trifluoroethyl) ether, 1,1,2-trifluoroethyl-2,2,2-trifluoroethyl ether, bis(1,1,2,2-tetrafluoroethyl) ether, and the like.

[0036] Among the above-mentioned fluorinated ethers (fluorine-containing chain ethers), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is preferred from the viewpoints of voltage resistance, boiling point, and the like.

[0037] The fluorinated ether may be contained in an amount of 50% by mass or more and 90% by mass or less, more preferably 75% by mass or more and 90% by mass or less, based on the total mass of the solvent. By making the amount of the fluorinated ether 75% by mass or more and 90% by mass or less, based on the total mass of the solvent, when aluminum is used as the positive electrode current collector 11, for example, corrosion of the aluminum by the electrolyte can be prevented. This makes it possible to further improve the charge / discharge cycle of the lithium ion battery 10. The concentration of the fluorinated ether in the electrolyte may be in the range of 1 mol / L or more and 5 mol / L or less.

[0038] Examples of the salt containing lithium dissolved in the solvent of the electrolyte include lithium imide compounds. The lithium imide compounds are generally produced by the reaction of lithium amide with lithium hydride. Examples of the lithium imide compounds used in the present embodiment include lithium bis-fluorosulfonylimide (LiFSI) and lithium bis-trifluoromethanesulfonylimide (LiTFSI). By adding such lithium bisimide as a lithium salt to a non-aqueous electrolyte, it is possible to improve low-temperature output characteristics and suppress the decomposition of the positive electrode surface that may occur during high-temperature cycle operation, thereby preventing the oxidation reaction of the electrolyte.

[0039] Such a lithium imide compound may be contained in the entire electrolyte solution in a concentration range of 1 mol / L or more and 3 mol / L or less.

[0040] A preferred composition ratio of the solvents, selected by the method for selecting an electrolyte material of the present invention described later, is LiFSI:EC:DME:TTE=1.4:0.2:2.0:3.0 (mol / L).

[0041] When the electrolyte solution of this embodiment having the above-mentioned configuration is used in the lithium-ion battery 10 of this embodiment, the particles of the positive electrode active material constituting the positive electrode active material layer 12 are covered with a film containing fluorine. For example, a fluorine-containing film is formed on the surface of the particles of the positive electrode active material by the fluorinated ether of the electrolyte. In this way, when the particle surface of the positive electrode active material is covered with a film of an inorganic material containing fluorine, the occurrence of damage such as cracking of the particles of the positive electrode active material can be suppressed even after the charge-discharge cycle has passed. This makes it possible to obtain good discharge characteristics in the charge-discharge cycle. In addition, by improving the stability of the surface of the positive electrode active material, oxygen release at high temperatures can be delayed, and the heat generation start temperature can be made higher, thereby improving high temperature resistance and safety.

[0042] As described above, the lithium-ion battery 10 using the optimal electrolyte material selected by the electrolyte material selection method described below can reduce capacity degradation due to charge / discharge cycles, and can realize a lithium-ion battery 10 with excellent durability. In addition, heat generation in the positive electrode 13 due to discharge is suppressed, and a lithium-ion battery 10 with even higher safety can be realized.

[0043] [How to select electrolyte materials] In the lithium ion battery 10 having the above-described configuration example, the method for selecting the electrolyte material (electrolyte solution) of this embodiment, which can improve the particle strength of the positive electrode active material and thereby suppress capacity degradation even after repeated charging and discharging, is as follows.

[0044] First, a solvent constituting an electrolyte material and a salt containing lithium, as exemplified in the configuration example of the lithium ion battery described above, are selected, and the salt containing lithium is dissolved in the solvent to form a candidate electrolyte material (electrolyte solution). At this time, the composition of the solvent used, the type of salt containing lithium, and the dosage of each are recorded for each electrolyte solution formed.

[0045] Next, a positive electrode and a negative electrode are formed for each electrolyte candidate material to form a lithium ion battery for evaluation as a sample. At this time, the positive electrode current collector and positive electrode active material constituting the positive electrode, and the negative electrode current collector and negative electrode active material constituting the negative electrode are formed using the same materials and in the same dosage in order to compare each lithium ion battery for evaluation with each other.

[0046] Then, the lithium ion batteries for evaluation thus formed are repeatedly charged and discharged under the same conditions (charge and discharge step). For example, the charge and discharge may be repeatedly performed at a predetermined atmospheric temperature, under constant discharge conditions, and under constant charge conditions.

[0047] As described above, each of the evaluation lithium ion batteries that have been charged and discharged a predetermined number of times under the same conditions is disassembled, and the used positive electrode active material is removed (removal process). For example, the evaluation lithium ion batteries after the cycle test are disassembled, the positive electrode current collector is scraped off, and an organic solvent is added to remove the binder. Thereafter, the positive electrode particles are scraped off and centrifuged to remove the carbon conductive additive. This allows the production of particles of the positive electrode active material that are samples used in particle hardness measurements, which will be described later.

[0048] Next, the particle hardness of the positive electrode active material constituting each of the evaluation lithium ion batteries taken out in the removal step is measured. In a method for measuring particle hardness, for example, particles of the positive electrode active material to be measured are placed on a stage as shown in Fig. 2. Then, a compressive load is applied to the particles of the positive electrode active material using, for example, a flat indenter made of diamond.

[0049] Then, a load-displacement diagram as shown in Figure 3 is obtained. The particle breaking strength (particle hardness) is calculated from the load and particle diameter at the brittle fracture point of the obtained load-displacement diagram. The particle breaking strength can be calculated from the following formula (1). Particle breaking strength (MPa) = πd 2 / 2.8P ···(1) Where, P: breaking load (N), d: particle diameter (mm)

[0050] Based on the particle hardness of each positive electrode active material obtained in the above manner, the electrolyte candidate material corresponding to the used positive electrode active material having the highest particle hardness is selected as the optimal electrolyte material (selection step). If a lithium ion battery is formed using the electrolyte material selected in this manner, it is possible to obtain a lithium ion battery in which damage to the particles of the positive electrode active material is suppressed even when repeated charging and discharging is performed, and the capacity does not decrease significantly even after repeated charging and discharging.

[0051] Although the embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and spirit of the invention. EXAMPLES

[0052] The method for selecting the electrolyte material of the present invention was verified. [Electrolyte layer] Electrolyte candidate materials (samples) 1 and 2 with the following compositions were prepared. Note that the concentration of each sample is shown relative to the concentration of the entire electrolyte. (Candidate material 1) Electrolyte: LiFSI (1.4 mol / L), Solvent: EC / DMC / TTE (0.2 / 2.0 / 3.0 mol / L) (Candidate material 2) Electrolyte: LiPF6 (1.2 mol / L), Solvent: EC / EMC / DMC (4.0 / 3.1 / 3.4 mol / L) LiFSI: Lithium bis-fluorosulfonyl imide LiPF6: Lithium hexafluorophosphate EC: Ethylene carbonate DMC: Dimethyl carbonate TTE: 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether EMC: Ethyl methyl carbonate The electrolyte solution of each sample was impregnated into a sheet-shaped porous substrate to obtain an electrolyte layer.

[0053] [Positive electrode] A mixture of LiCoNiMnO6 (NMC), lithium carbonate, Ketjen black (KB), and polyvinylidene fluoride (PVdF) was used as the positive electrode material. This mixture was applied to a thin aluminum film using a coating machine (blade coater), and then dried to obtain a positive electrode.

[0054] [Negative electrode] The negative electrode was made of graphite and silicon oxide.

[0055] The positive electrode, negative electrode, and electrolyte layer were laminated as described above to prepare lithium ion batteries 1 and 2 for evaluation. Then, 500 cycles of charge and discharge were performed at a temperature of 25° C. using evaluation lithium ion batteries 1 and 2, which were prepared using the electrolyte solutions of the above-mentioned candidate materials 1 and 2, respectively.

[0056] After that, each of the evaluation lithium-ion batteries 1 and 2 was disassembled, the positive electrode current collector was scraped off, an organic solvent was added to remove the binder, and then the positive electrode particles were scraped off and centrifuged to remove the carbon conductive additive. In this way, particles of used positive electrode active material constituting each of the evaluation lithium-ion batteries 1 and 2 were obtained.

[0057] <Verification example 1> As a verification example 1, the particle fracture strength (particle hardness) of particles of the used positive electrode active material of each of the above-mentioned evaluation lithium ion batteries 1 and 2 was measured. The measurement was performed using a measuring device shown in FIG. 2, and the particle fracture strength (particle hardness) was calculated by the above-mentioned formula 1 based on the measured brittle fracture point.

[0058] The particle fracture strength (particle hardness) of particles of used positive electrode active material obtained using these candidate materials 1 and 2 is shown in the graph in Figure 4. In addition, for reference, the particle fracture strength (particle hardness) of particles of the positive electrode active material before the charge-discharge cycle is also shown.

[0059] According to the results shown in Figure 4, it was confirmed that evaluation lithium-ion battery 1 created using candidate electrolyte material 1 has particles of positive electrode active material coated with a film derived from LiFSI, and therefore has about seven times the particle destruction strength (particle hardness) even after 500 cycles of charge and discharge compared to evaluation lithium-ion battery 2 created using candidate electrolyte material 2. This confirmed that if a lithium-ion battery is formed using an electrolyte with the composition of candidate electrolyte material 1, particle damage of the positive electrode active material is suppressed even after repeated charge and discharge, and a lithium-ion battery without a significant decrease in capacity can be obtained.

[0060] <Verification example 2> As a verification example 2, a thin sample of the positive electrode of each of the above-mentioned evaluation lithium-ion batteries 1 and 2 was prepared. Then, each of the thin samples was observed using a scanning transmission electron microscope (STEM) at an acceleration voltage of 200 kV. The obtained observation images were subjected to a qualitative analysis of the constituent elements near the surface of the positive electrode using energy dispersive X-ray analysis (EDX). The results are shown in FIG. 5.

[0061] According to the results shown in FIG. 5, in the evaluation lithium-ion battery 1 created using the candidate electrolyte material 1, a large amount of fluorine was detected on the surface of the positive electrode particles, and it was confirmed that the positive electrode particles were covered with a fluorine coating.

[0062] <Verification example 3> As a verification example 3, the cross-sections of the positive electrodes of the above-mentioned evaluation lithium-ion batteries 1 and 2 were processed by ion polishing to prepare cross-sectional observation samples. Then, the cross-sections of the cross-sectional observation samples were observed using a scanning electron microscope (SEM) at an acceleration voltage of 5 kV. Then, the number of damaged and undamaged positive electrode particles was quantified from the cross-sectional observation images. FIG. 6 shows SEM images of each of the positive electrodes and a graph showing the reduction rate of undamaged positive electrode particles due to charge / discharge cycles.

[0063] According to the results shown in Figure 6, the number of particle cracks in the positive electrode of evaluation lithium-ion battery 2 made using candidate electrolyte material 2 increased significantly after the cycle test, whereas the increase in the number of particle cracks in the positive electrode of evaluation lithium-ion battery 1 made using candidate electrolyte material 1 was small. In addition, since a correlation was observed between the capacity decrease rate in the cycle test and the number of particle cracks, it is believed that the capacity degradation of the battery can be suppressed by suppressing particle cracks in the positive electrode.

[0064] The criteria for determining whether or not the positive electrode particles have cracks were as follows: clear cracks, as in image (a) of Figure 7, were considered to be cracked, and particles with holes, as in images (b) and (c), were considered not to be cracked. [Industrial Applicability]

[0065] The method for selecting an electrolyte material of the present invention uses a plurality of candidate electrolyte materials to form lithium ion batteries for evaluation, and after charging and discharging these lithium ion batteries for evaluation under the same conditions, evaluates the particle hardness of the positive electrode active material, thereby making it possible to easily select an electrolyte material that is optimal for preventing capacity degradation. This makes it easy to develop a lithium ion battery with less capacity degradation. Therefore, the method has industrial applicability. [Explanation of symbols]

[0066] 10...Lithium-ion battery 11...Positive electrode current collector 12...Cathode active material layer 13…Positive electrode 14…Negative electrode current collector 15…Negative active material layer 16…Negative electrode 17…Electrolyte layer

Claims

1. A method for selecting an electrolyte material for a lithium ion battery having a positive electrode having a positive electrode current collector and a positive electrode active material, a negative electrode having a negative electrode current collector and a negative electrode active material and facing the positive electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode and containing an electrolyte material, comprising: A charging and discharging step of charging and discharging under the same conditions using a plurality of evaluation lithium ion batteries each including a plurality of candidate electrolyte materials having ion conductivity and the positive electrode active material in an unused state; a removal step of removing a used positive electrode active material from each of the plurality of evaluation lithium ion batteries that have been subjected to the charge / discharge step; a selection step of measuring hardness of the particles of the plurality of used positive electrode active materials removed in the removal step, and selecting, as the electrolyte material, the candidate electrolyte material corresponding to the used positive electrode active material having the highest hardness.

2. 2. The method for selecting an electrolyte material according to claim 1, wherein the positive electrode active material contains a composite oxide of lithium and a transition metal.

3. 3. The method of claim 2, wherein the transition metal includes at least one of nickel, cobalt, and manganese.

4. 3. The method for selecting an electrolyte material according to claim 1, wherein the electrolyte material is selected from a solvent containing either ethylene carbonate or dimethyl carbonate, and a salt containing lithium dissolved in the solvent.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery, method for producing the same, and positive electrode for secondary battery including the same

    JP2022510653A